Fragmentary ancestors? Medicine, bodies, and personhood in a Koma Mound, Northern Ghana - Insoll, T.; Kankpeyeng, B.W.; Nkumbaan, S.N. (Archaeology of Spiritualities, 2012)
Excavation of a single mound at Yikpabongo, Koma Land, northern Ghana, recovered a signi fi cant assemblage of ceramic fi gurines and fi gurine parts radiocarbon dated to the early second millennium ad . Rather than haphazard deposition of waste materials, the contextual arrangements suggest meaningful intention, and that the mound might have been a shrine, possibly linked in part to a medicinal or healing function. Potentially, signi fi cant statements were also being made about bodies and persons via the fi gurines, their fragmentation and selection, and their association with selected human remains-skulls, teeth, long bones-and other materials-pottery, lithics, iron, and glass beads. Complex beliefs seemingly underpinned these actions and this is explored in relation to the concept of the ancestors and how this might have helped structure past personhood and ontology. © Springer Science+Business Media New York 2012.
Keywords: Human Remains; Ritual Action; Tooth Filing; Ethnolinguistic Group; Ethnographic Analogy